A partial analysis of ocean health index based on clean waters and biodiversity goals in Ambon and Baguala bays, Maluku - Irma Kesaulya; Sara Haumahu; Victor P.H. Nikijuluw; Cilun Djakiman (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2024)
It is important to maintain a healthy marine ecosystem to support eco-friendly and sustainable fishery development. Implementation of Ocean Health Index (OHI) started globally in 2012, and it has been strongly recommended to be conducted at all levels: locally, nationally, and regionally. Indonesia has modified OHI for its national assessment, which its called Indeks Kesehatan Laut Indonesia (IKLI). IKLI has been estimated since 2020 and introduction applied at the sub-national level. This study is an attempt to implement IKLI in Maluku province with the main objective is to estimate score of a partial IKLI, based on clean waters (goal no. 9) and biodiversity (goal no. 10). Samples were taken from Ambon and Baguala Bays between June and September 2022. For clean water goals, the parameters used were concentration of phosphate, nitrate, silicate, dissolved oxygen (DO), pH, and the number of ports that implemented green principles. The parameters of water quality of silicate, DO and pH in those two bays are within the range of government-mandated standards, except for nitrate and phosphate concentrations which are not. For the biodiversity goal, the parameters used are the species composition of mangrove, seagrass, fish, and coral. The IKLI biodiversity score was low due to the high level of human activity pressure at the two selected study sites. This study demonstrates the applicability of the IKLI in a partial analysis, and its usefulness in highlighting existing data and knowledge gaps. The study suggests that a comprehensive IKLI assessment should be conducted in Maluku Province. Meanwhile to improve the national-level IKLI assessment, actions should prioritize improving water quality management, expanding marine protected areas, and monitoring coastal ecosystems, especially those heavily affected by human activities.KeywordsArchipelagonutrientOHIIKLI Maluku